Fireside corrosion on T24 steel pipes and HVOF NiCr coatings exposed to different salt mixtures. (15th August 2020) - Abu-warda, N.; López, A.J.; Pedraza, F.; Utrilla, M.V.
Graphical abstract: Highlights: Fireside corrosion behavior of T24 steel and HVOF-NiCr coating was evaluated. Salts mixtures based on NaCl, KCl, Na2 SO4 and K2 SO4 were studied at 650 °C. The presence of chlorides decreased the corrosion resistance of NiCr coating. Corrosion mechanisms for each salt mixture were obtained. Abstract: Fireside corrosion of T24 steel and HVOF NiCr-coated counterparts is investigated. The samples were exposed to different deposits of NaCl, KCl, Na2 SO4 and K2 SO4 at 650 °C for 360 h in dry air. The deposit with the highest chloride content (NaCl-KCl) was the most aggressive followed by the ones combining chlorides and sulfates. In contrast, the sulfate-based salts did not produce severe damage. The NiCr coating maintained the integrity of the substrate but the chlorides induced a great attack on the coating. The formation of K2 CrO4 and the penetration of chlorides are identified as the main factors of this attack.